2024
DOI: 10.1021/acs.jproteome.3c00754
|View full text |Cite
|
Sign up to set email alerts
|

Data-Independent Acquisition Proteomics and N-Terminomics Methods Reveal Alterations in Mitochondrial Function and Metabolism in Ischemic-Reperfused Hearts

Bridgette Hartley,
Wesam Bassiouni,
Andrej Roczkowsky
et al.

Abstract: Myocardial ischemia-reperfusion (IR) (stunning) injury triggers changes in the proteome and degradome of the heart. Here, we utilize quantitative proteomics and comprehensive degradomics to investigate the molecular mechanisms of IR injury in isolated rat hearts. The control group underwent aerobic perfusion, while the IR injury group underwent 20 min of ischemia and 30 min of reperfusion to induce a stunning injury. As MMP-2 activation has been shown to contribute to myocardial injury, hearts also underwent I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
1
1
0
Order By: Relevance
“…To assess the biological implications of the identified substrates, we compared our data to the literature on hypoxia-reoxygenation or ischemia-reperfusion injury in the heart or cardiomyocytes. We then compared substrates identified here to those cleaved by MMP-2 in vitro. In addition, we took into account our accompanying paper, describing the degradome changes that occur during cardiac ischemia-reperfusion injury in rat hearts (Table S2, Supporting Information). By comparing the results between these studies, we identified multiple proteins that were cleaved at the same site following ischemia-reperfusion injury and by MMP-2-Fc-induced proteolysis in ventricular extracts.…”
Section: Resultssupporting
confidence: 53%
“…To assess the biological implications of the identified substrates, we compared our data to the literature on hypoxia-reoxygenation or ischemia-reperfusion injury in the heart or cardiomyocytes. We then compared substrates identified here to those cleaved by MMP-2 in vitro. In addition, we took into account our accompanying paper, describing the degradome changes that occur during cardiac ischemia-reperfusion injury in rat hearts (Table S2, Supporting Information). By comparing the results between these studies, we identified multiple proteins that were cleaved at the same site following ischemia-reperfusion injury and by MMP-2-Fc-induced proteolysis in ventricular extracts.…”
Section: Resultssupporting
confidence: 53%
“…High-resolution imaging techniques like MRI and PET are used to provide real-time, detailed images of cardiac function, while integration with bioengineering has led to the development of 3D-printed heart tissues and organs-on-chips that simulate more realistic cardiac physiology [ 50 52 ]. Additionally, advanced genomic and proteomic techniques allow for detailed analysis of changes within the heart under various conditions, aiding in the discovery of new therapeutic targets [ 53 ]. Moreover, the isolated perfusion model expands opportunities for targeted immunomodulation, building tolerance to ischemia-reperfusion injury, and correcting pathogenic genetic defects.…”
Section: Current Uses and Future Perspectives Of Isolated Heart Perfu...mentioning
confidence: 99%